Engendering Hope: A Person-Centred Reflection on Technology and Gender†. Issue 1 (2nd January 2016) - Waters, Simon
Abstract : This paper examines instances of recent musical and artistic works and asks to what extent it makes sense to regard certain practices and technologies as gendered. It looks at a number of strategies for making, suggesting that male gender stereotypes are as prevalent and unhelpful (to practitioners) as female ones. It looks at aspects of the working environments of practitioners to determine whether changes in such conditions might alleviate the gender mismatch in enrolment in higher education courses featuring ubiquitous technologies. The paper identifies historical precedents for technology gendering in which readings of such gendering have shifted radically, suggesting they offer scope for optimism in our longer-term reading of the gendered-ness of current practices. The paper also touches on the extent to which a 'research' ethos––the foregrounding of the essential human attributes of inquisitiveness and empathy––may contribute to our capacity to tell better, less binary stories of otherness in all its forms.